Considerations in performing odontectomy under general anesthesia: case series - Anindita Zahratur Rasyida; Andra Rizqiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: An odontectomy constitutes a common surgical procedure performed by oral and maxillofacial surgeons on a daily basis. The anesthesia procedure required during this form of operation may involve the administering of a general anesthesia which, while a safe procedure when performed by an anesthesiologist, still involves an element of risk and should only be undertaken with appropriate safeguards. Various measures, not only anxiety control-based, are suggested in this article. Purpose: The purpose of this study was to report considerations factors, other than anxiety, as indications in performing odontectomy conducted under a general anesthesia at Universitas Airlangga Hospital, Surabaya, Indonesia. Cases: Four cases of patients who had undergone an odontectomy under a general anesthetic are reported here. Case management: The four cases of management involved odontectomies conducted under a general anesthetic for a variety of reasons with contrasting outcomes. The treatment of the four patients was based on an anatomical approach and previously ineffective pain control due to greater trauma. One of the patients also suffered from schizophrenia that produced comorbidity requiring holistic observation. This individual required intricate surgery whose performance was challenging under a local anesthetic. None of our other patients suffered from serious complications related either to surgery or the administering of a general anesthetic. Conclusion: In conclusion, important factors relating to an odontectomy performed under a general anesthetic on four patients in Universitas Airlangga Hospital, Surabaya included: anxiety, anatomical approach, adequate pain control, comorbidity of systemic medical conditions and the potential need for surgical procedures difficult to perform under a local anesthetic.